Fourteen Day In Vivo Testing of a Compliant Thoracic Artificial Lung. Issue 5 (September 2017) - Skoog, David J.; Pohlmann, Joshua R.; Demos, David S.; Scipione, Christopher N.; Iyengar, Amit; Schewe, Rebecca E.; Suhaib, Ahmed B.; Koch, Kelly L.; Cook, Keith E.
Abstract : The compliant thoracic artificial lung (cTAL) has been studied in acute in vivo and in vitro experiments. The cTAL's long-term function and potential use as a bridge to lung transplantation are assessed presently. The cTAL without anticoagulant coatings was attached to sheep (n = 5) via the pulmonary artery and left atrium for 14 days. Systemic heparin anticoagulation was used. Compliant thoracic artificial lung resistance, cTAL gas exchange, hematologic parameters, and organ function were recorded. Two sheep were euthanized for nondevice-related issues. The cTAL's resistance averaged 1.04 ± 0.05 mmHg/(L/min) with no statistically significant increases. The cTAL transferred 180 ± 8 ml/min of oxygen with 3.18 ± 0.05 L/min of blood flow. Except for transient surgical effects, organ function markers were largely unchanged. Necropsies revealed pulmonary edema and atelectasis but no other derangements. Hemoglobin levels dropped with device attachment but remained steady at 9.0 ± 0.1 g/dl thereafter. In a 14 day experiment, the cTAL without anticoagulant coatings exhibited minimal clot formation. Sheep physiology was largely unchanged except for device attachment-related hemodilution. This suggests that patients treated with the cTAL should not require multiple blood transfusions. Once tested with anticoagulant coatings and plasma resistant gas exchange fiber, the cTAL could serve as a bridge to transplantation.